Budget Impact of Belantamab Mafodotin (Belamaf) Adoption in the Treatment of Patients with Relapsed or Refractory Multiple Myeloma in the United States - Shah A; Tosh JC; Ambavane A; Nikolaou A; Hogea C; Samyshkin Y; Gorsh B; Maiese EM; Wang F (Dove Medical Press, 2021)
Anshul Shah,1 Jonathan C Tosh,2 Apoorva Ambavane,2 Andreas Nikolaou,2 Cosmina Hogea,3 Yevgeniy Samyshkin,4 Boris Gorsh,3 Eric M Maiese,5 Feng Wang3 1Modelling and Simulation, Evidera, Waltham, MA, USA; 2Modelling and Simulation, Evidera, London, UK; 3Value Evidence and Outcomes, GlaxoSmithKline, Upper Providence, PA, USA; 4Value Evidence and Outcomes, GlaxoSmithKline, Brentford, UK; 5Value Evidence and Outcomes, GlaxoSmithKline, Philadelphia, PA, USACorrespondence: Anshul ShahEvidera, 500 Totten Pond Road, Suite 500, Waltham, MA, 02451, USATel +1 781 640 8941Email Anshul.shah@evidera.comPurpose: Estimate the budget impact of belantamab mafodotin (belamaf) for patients with relapsed/refractory multiple myeloma (RRMM) who have received ≥ 4 prior therapies, including an anti-CD38 monoclonal antibody, a proteasome inhibitor, and an immunomodulatory agent.Methods: A budget impact analysis (BIA) was developed to estimate the cost difference between current (no belamaf) and projected (with belamaf) market scenarios over 3 years. Comparators were identified from a systematic literature review and included selinexor + dexamethasone or best supportive care. The number of treatment-eligible patients were estimated using an epidemiology model. Base-case analyses were conducted from a US commercial payer perspective (cost year: 2019). Model inputs included market share estimates, treatment duration, and costs of drug acquisition/administration, concomitant medications, adverse event (AE) management, treatment monitoring, and subsequent treatments based on published literature/cost databases. Budget impact, calculated as the difference in costs between current and projected scenarios over 3 years, was reported as cost per member per month (PMPM) and per member per year (PMPY). One-way sensitivity analysis assessed which key parameters most affected model outcomes. Alternative scenarios were tested (1- or 5-year time horizon; Medicare perspective; negligible cost of mental status change AE).Results: In a hypothetical commercial payer health plan with 1 million members, 33 patients were identified as treatment-eligible over 3 years. Introducing belamaf for patients with RRMM resulted in an estimated budget-neutral PMPM cost of −